Contextualizing Maqāṣid al-Sharī‘ah in Indigenous Legal Practices: A Comparative Study of Family Resilience in Kasepuhan Ciptagelar and Kampung Naga - Rozikin, Opik; Oyo Sunaryo Mukhlas; Aden Rosadi; Ine Fauzia; Muharir, Muharir; Ahyani, Hisam; Nurul Ilyana Muhd Adnan (Nurani, 2025)
Strengthening the normative foundation and maqāṣid orientation of Indonesia’s religious court system allows it to render fair judgments for the parties while safeguarding the future of children. While Islamic family law is often studied normatively, limited attention is given to its lived application in plural legal settings. Using a descriptive qualitative approach with socio-legal and phenomenological methods, data were collected through purposive sampling of 20 participants, including traditional leaders, religious figures, and village officials. Field observations and the analysis of local documents, including customary manuscripts, sermons, and marriage records, serve to complement the data. The findings reveal that family resilience emerges from a dynamic interplay between Islamic and customary norms, particularly in areas like inheritance, marriage, and gender roles. Integration of maqāṣid al-sharī‘ah occurs through contextual reinterpretation aligned with communal structures and values. Differences between the communities are notable in the role of traditional authority, the interpretation of qiwāmah, and dispute resolution mechanisms. This study contributes to the discourse on Islamic legal pluralism by presenting a contextual model of normative integration. It highlights the potential of a culturally grounded and adaptive Islamic legal framework to strengthen sustainable family systems across diverse local contexts.